2017
DOI: 10.4253/wjge.v9.i12.571
|View full text |Cite
|
Sign up to set email alerts
|

Lumen-apposing metal stents for benign gastrointestinal tract strictures: An international multicenter experience

Abstract: AIMTo investigate technical feasibility, outcomes and adverse events of the lumen-apposing metal stent (LAMS) for benign gastrointestinal (GI) tract strictures.METHODSBetween July 2015 and January 2017, patients undergoing treatment by LAMS for benign GI strictures at three tertiary referral centers were included in this study. Primary outcomes included technical success, short-term clinical success, long-term clinical success, and adverse events. Short-term clinical success was defined as symptom resolution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 19 publications
2
30
0
2
Order By: Relevance
“…Other studies, such as those of Bazerbachi et al [37] or Santos-Fernandez et al [38], report higher stent migration rates (17.9 and 19%, respectively), at the expense of those implanted for colon strictures. Nonetheless, this complication is considerably less than that observed with conventional metal stents.…”
Section: Endoscopy -Novel Techniques and Recent Advancementsmentioning
confidence: 90%
See 1 more Smart Citation
“…Other studies, such as those of Bazerbachi et al [37] or Santos-Fernandez et al [38], report higher stent migration rates (17.9 and 19%, respectively), at the expense of those implanted for colon strictures. Nonetheless, this complication is considerably less than that observed with conventional metal stents.…”
Section: Endoscopy -Novel Techniques and Recent Advancementsmentioning
confidence: 90%
“…This characteristic led to its use in the treatment of benign strictures of the digestive tract. Several studies have assessed its usefulness, although with only a few patients and mostly concerning benign strictures of the upper digestive tract; however, some include postsurgical colon strictures [35][36][37][38]. The clinical success rate improves significantly as compared with the traditional covered metal stents, reducing the rate of stent migration and with a lower complication rate.…”
Section: Novel Treatments: Lumen-apposing Metal Stentsmentioning
confidence: 99%
“…1). To date, 22 patients in the reviewed literature had a LAMS placed for an esophageal stricture [13][14][15][16]. Anastomotic strictures were the most common indication, seen in 17 of the 22 patients.…”
Section: Esophageal Stricturesmentioning
confidence: 99%
“…Santos-Fernandez et al reported 9 patients with esophageal strictures treated with a LAMS [14]. LAMS were left in place for 60 days or more and only 3 patients had symptom improvement or resolution after stent removal with the stent in place for longer than 60 days.…”
Section: Esophageal Stricturesmentioning
confidence: 99%
See 1 more Smart Citation